w+27=(-64)

Simple and best practice solution for w+27=(-64) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for w+27=(-64) equation:


Simplifying
w + 27 = (-64)

Reorder the terms:
27 + w = (-64)
27 + w = -64

Solving
27 + w = -64

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + w = -64 + -27

Combine like terms: 27 + -27 = 0
0 + w = -64 + -27
w = -64 + -27

Combine like terms: -64 + -27 = -91
w = -91

Simplifying
w = -91

See similar equations:

| 2/x-22=5/x-2 | | x/7-1=2 | | m-68=-48 | | -5=j+5 | | q-(-9)=73 | | 14c-7d= | | 98=-7z | | 2v-15=25 | | -15=w-62 | | 3x+14=-7+2x | | -4n=(-64) | | 10x^2+81x+8=0 | | h+(-91)=6 | | -8j=88 | | c^2-3c-85=0 | | 10x-11-8x+23=6 | | -9h=-99 | | b-(-12)=15 | | -4u-2(-u-15)=8(2u-9) | | 3=j+-9 | | 17=c-(-7) | | 6n^2+29n+28=0 | | 3Cosx=3 | | 12=-4g | | 6x-10-4x+13=-2 | | 15=s-(-4) | | 16-10/2 | | 9n^2+36n+20=0 | | a*6-1=10 | | 1,430/2=t/5 | | b-(-55)=62 | | 3/4x-1/3x=1/12 |

Equations solver categories